2017
DOI: 10.3762/bjnano.8.93
|View full text |Cite
|
Sign up to set email alerts
|

High photocatalytic activity of Fe2O3/TiO2nanocomposites prepared by photodeposition for degradation of 2,4-dichlorophenoxyacetic acid

Abstract: Two series of Fe2O3/TiO2 samples were prepared via impregnation and photodeposition methods. The effect of preparation method on the properties and performance of Fe2O3/TiO2 for photocatalytic degradation of 2,4-dichlorophenoxyacetic acid (2,4-D) under UV light irradiation was examined. The Fe2O3/TiO2 nanocomposites prepared by impregnation showed lower activity than the unmodified TiO2, mainly due to lower specific surface area caused by heat treatment. On the other hand, the Fe2O3/TiO2 nanocomposites prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 46 publications
1
24
1
Order By: Relevance
“…4(a), it was confirmed that the P25 TiO 2 showed strong emission spectrum with emission peaks at 410, 465, and 544 nm. It has been reported that the peak around 410 nm would correspond to the radiative recombination of self-trapped exciton and the other two emission peaks at 465 and 544 nm would be due to the charge transfer of an oxygen vacancy trapped electron [11]. Addition of CoO did not give the formation of any new emission peaks, but decreased the emission intensity of the bare P25 TiO 2 ( Fig.…”
Section: Properties Of Photocatalystsmentioning
confidence: 91%
See 4 more Smart Citations
“…4(a), it was confirmed that the P25 TiO 2 showed strong emission spectrum with emission peaks at 410, 465, and 544 nm. It has been reported that the peak around 410 nm would correspond to the radiative recombination of self-trapped exciton and the other two emission peaks at 465 and 544 nm would be due to the charge transfer of an oxygen vacancy trapped electron [11]. Addition of CoO did not give the formation of any new emission peaks, but decreased the emission intensity of the bare P25 TiO 2 ( Fig.…”
Section: Properties Of Photocatalystsmentioning
confidence: 91%
“…The excited electrons would react with adsorbed oxygen to produce superoxide radicals, while holes would oxidize 2,4-D. Holes could also oxidize water to produce hydroxyl radicals. However, the contribution of hydroxyl radicals to degrade 2,4-D would not be as high as those of superoxide radicals and holes due to the low formation of hydroxyl radicals [11]. In addition to this pathway, electrons could be also trapped by cobalt species, which in turn caused a better separation of electrons and holes, and thus, higher photocatalytic activity.…”
Section: Photocatalytic Activity and Proposed Mechanismmentioning
confidence: 99%
See 3 more Smart Citations